Predictor of instant messaging use among students for academic purpose - Roslan, Nur Ain Nabilah; Mohd Ayub, Ahmad Fauzi; Ghazali, Norliza (International Association of Online Engineering, 2020)
This study was carried out to identify the predictors of instant messaging use for academic purposes among undergraduates at Faculty of Educational Studies in Universiti Putra Malaysia (UPM). Predictors studied were perceived usefulness, perceived ease of use, perceived enjoyment, perceived convenience, attitude toward use and behavior intention to use instant messaging for academic purposes. A total of 285 samples were selected from undergraduates. Data were collected in a quantitative manner using a questionnaire. The inferential statistic confirmed the significant positive relationship between perceived usefulness, perceived ease of use, perceived enjoyment, perceived convenience, attitude toward use and behavior intention with the use of instant messaging for academic purposes. All relationship was identified as moderate. Also, the multiple linear regressions analysis was used to identify predictors of six independent variables that contributed towards the use of instant messaging. Finally, the results showed the predictors of instant messaging use for academic purposes amongst students were the perceived usefulness, perceived convenience and attitude towards the use of instant messaging. The study indicated that when students feel by using the instant messaging is useful and convenience to them, they will use it. Besides that, positive attitudes towards using instant messaging is among critical factor for the students to use it. This finding further suggests that students in general positively view of instant messaging as a useful tool that supports them in communicating between peers and lecturers. This further suggests that instant messaging platforms are likely to have a positive perception and students feel pleased to use instant messaging as tools of communication.